Management of Atmosphere Resources in Hydrometeorological Disaster Mitigation - F Heru Widodo; Tukiyat Tukiyat; R Djoko Goenawan (Universitas Sebelas Maret, 2020)
Hydrometeorological disaster management in Indonesia such as floods, drought, tornadoes, etc., which occur almost every year in Indonesian territory, is carried out with structural efforts, however, it seems that the occurrence of disasters is still occurring even the intensity is increasing. To minimize the occurrence of hydrometeorological disasters, it is necessary to try a non-structural approach, namely the Weather Modification Technology (WMT). The application of WMT for hydrometeorological disaster mitigation can be used as an alternative solution in disaster risk reduction in Indonesia. The current WMT can be used to increase rainfall, to reduce rainfall, to mitigate floods and to reduce smoke due to forest and land fires. The application of WMT for additional rainfall is able to increase rainfall by about 30%, while to reduce rainfall, it can reduce rainfall by about 30-35%. This technology can be used as an integral part in the management of water resources in Indonesia.